The Philosophical Foundations of the Researches of the Inclusive Education - Hryhoriy Vasianovych; Olena Budnyk (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
In the article on the basis of primary sources the philosophical foundations of the modern inclusive education are examined. The content description of the idea “inclusive education” is presented, the necessity of its implementation is proved. It is focused on two basic philosophical foundations of its development: personalism and intuitionism. Such an approach is caused by the fact that in modern studies on the above-mentioned range of problems are mainly dominated by rationalist methodological approaches, in contrast with the irrationalistic theories are often out of the attention. In our analysis and interpretation, the philosophy of personalism plays an important methodological role because it helps clarify the essence of the uniqueness and originality of each child with special needs and to determine the real ways of her spiritual and psychophysical development. The philosophy of intuitionalism focuses on the study of issues related to the formation of consciousness of a person with special needs. Therefore, the authors proved the necessity of using the intuitive method of research, which allows to promote the communication of subjects of interaction actively, to reveal their spiritual potential, to perform the search for ways of forming thinking in children with special needs, use the language, culture and art at the same time and in an active way.